Reimaging America: The Arts of Social Change and The Autobiography of Malcolm X. - Watts, Linda S. (Radical Teacher, 2019)
In a course on literary analysis and theory, Watts asks students to create and analyze a visual work based on passages they select from Malcolm X’s Autobiography.